Marion and the girls' getaway - Barkley, Callie (Barkley, Callie. Critter Club, 2019)
When Marion and the other members of the Critter Club plan a ski weekend, they meet a snow bunny on the slopes, but Marion's kitten, Ollie, scares the bunny away.